2022
DOI: 10.1371/journal.pone.0270107
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of postintubation dysphagia in ICU patients in the context of the COVID-19 outbreak: A report of 920 cases from a Brazilian reference center

Abstract: The purpose of this research was to identify risk factors that were independently related to the maintenance of a swallowing dysfunction in patients affected by critical COVID-19. We conducted a prospective observational cohort study of critical patients with COVID-19, who were admitted to a COVID-19 dedicated intensive care unit (ICU) and required prolonged orotracheal intubation (≥48 hours). Demographic and clinical data were collected at ICU admission and/or at hospital discharge or in-hospital death. Swall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Age-related atrophy of the soft tissues of the pharynx and larynx may also be considered a contributing factor to swallowing changes. 28 Considering stroke, studies have already described that increasing age is a strong predictive factor for a stronger and faster loss of muscle activities, increasing the incidence of dysphagia and mortality. 8 , 10 , 29 The present results show that both groups were composed of elderly patients but G1 had older participants, while G1 had a mean age of 72.9 years G2 had a mean age of 65.3.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related atrophy of the soft tissues of the pharynx and larynx may also be considered a contributing factor to swallowing changes. 28 Considering stroke, studies have already described that increasing age is a strong predictive factor for a stronger and faster loss of muscle activities, increasing the incidence of dysphagia and mortality. 8 , 10 , 29 The present results show that both groups were composed of elderly patients but G1 had older participants, while G1 had a mean age of 72.9 years G2 had a mean age of 65.3.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PED among patients with COVID-19 is similar to that stated in previous reports (22.4%–100%). 4 , 5 , 6 , 7 , 23 , 24 , 25 )…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PED among patients with COVID-19 is similar to that stated in previous reports (22.4%-100%). [4][5][6][7][23][24][25] Our results demonstrated that during the post-extubation period, daily median caloric and protein intakes increased from 6.9 kcal/kg per day (IQR, 3.5-10.2 kcal/kg per day) and 0.3 g/kg per day (IQR, 0.1-0.5 g/kg per day) at first BSE to 24.8 kcal/kg per day (IQR, 20.1-27.9 kcal/kg per day) and 1.1 g/kg per day (IQR, 0.9-1.2 g/kg per day), respectively, just before discharge. However, six patients showed caloric intakes that were less than 25 kcal/kg per day just before discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations